2004
DOI: 10.1111/j.1432-2277.2004.tb00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids analysis: a tool to assess graft function in human liver transplantation

Abstract: The expanding use of “sub‐optimal” grafts due to donor organ shortage increases the importance of accurate graft assessment before liver transplantation. Bile secretion is an early sign of recovering hepatic function post‐transplant. The role of bile acid analysis in assessing graft function before and immediately after liver transplantation has been investigated. Two hundred and sixteen samples of hepatic bile were collected from 35 donors and 13 recipients. Clinical data, bile flow, total bile acid concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…(41) A couple of years later, the same group showed that suboptimal donor livers had a different bile acid composition compared with standard grafts: a lower apparent choleretic activity (indicating that bile flow did not increase appropriately with increased bile acid output) and a lower ratio of CA/CDCA. (10) Increasing CA/CDCA ratios were observed after recovery from ischemia after LT. (34) Instead of graft assessment during machine perfusion, bile collected during procurement may have the potential to assess liver quality in DBD donors. However, studies on donor bile composition are currently limited, probably due to logistical challenges during procurement.…”
Section: Bile Composition Of the Donor Graft: Obtained During Procurementioning
confidence: 97%
See 2 more Smart Citations
“…(41) A couple of years later, the same group showed that suboptimal donor livers had a different bile acid composition compared with standard grafts: a lower apparent choleretic activity (indicating that bile flow did not increase appropriately with increased bile acid output) and a lower ratio of CA/CDCA. (10) Increasing CA/CDCA ratios were observed after recovery from ischemia after LT. (34) Instead of graft assessment during machine perfusion, bile collected during procurement may have the potential to assess liver quality in DBD donors. However, studies on donor bile composition are currently limited, probably due to logistical challenges during procurement.…”
Section: Bile Composition Of the Donor Graft: Obtained During Procurementioning
confidence: 97%
“…When conjugated bile acids enter the canaliculus, ). (10) In humans, up to 90% of bile flow is dependent on bile salts. Bile saltindependent bile flow can be stimulated by active solutes, such as glutathione and bicarbonate.…”
Section: How Bile Is Formedmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies where bile was analysed in detail greatly contributed to the understanding of the various aspects of OLTx per se as well as influences of immunosuppressive drugs/regimens, rejection, post‐operative complications and external biliary drainage (T‐tube). Suboptimal donor livers demonstrate an altered bile composition compared with normal grafts 11 . Immediately after transplantation, modifications of bile composition and volume depend on the duration and recovery from cold ischaemia (1–3 h), 12 while acute rejection 13 or immunosuppressive drugs 13 exert their effect later (7–14 days and 3–4 weeks, respectively).…”
Section: Liver Transplantationmentioning
confidence: 99%
“…Such modifications in bile composition are probably due to the influence of immunosuppressive drugs [28,29] . Both experimental [26,[29][30][31] and clinical studies [32][33][34] bile acid composition when compared to normal grafts [35] . Bile cytotoxicity (measured by an increase in the bile salt/phospholipid ratio) appears to be involved in the pathogenesis of non-anastomotic biliary strictures [36,37] .…”
Section: Liver Transplantationmentioning
confidence: 99%